PENGARUH PENERAPAN DISCHARD PLANNING PERAWAT TERHADAP PENGETAHUAN PENGELOLAAN NUTRISI PADA PASIEN DIABETES MELITUS TIPE 2 DI RUANG RAWAT INAP RSUD PROF DR.H. ALOE SABOE KOTA GORONTALO - Pipin Yunus; Haslinda Damansyah (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
This study is to investigate discard planning performed by the nurses with capability in organizing nutrition to diabetes type II patients. The design used is pre-experimental study with one group pre and post test design. The sample is 10 patients. The data is analyzed by using paired t test. The result shows that there is a significant relationship of discard planning performed by nurses with their capability in organizing nutrition to diabetes type II patients with value 0.000 ka= 0.05). it is suggested that the nurses should give discard planning treatment comprehensively to the patients before they go home.